Agile Processes in Software Engineering and Extreme Programming 14th International Conference, XP 2013, Vienna, Austria, June 3-7, 2013, Proceedings - Baumeister, Hubert.; Baumeister, Hubert.; Weber, Barbara.; Weber, Barbara. (Lecture Notes in Business Information Processing,, 2013)
This book contains the refereed proceedings of the 14th International Conference on Agile Software Development, XP 2013, held in Vienna, Austria, in June 2013. In the last decade, the interest in agile and lean software development has been continuously growing. Agile and lean have evolved from a way of working -- restricted in the beginning to a few early adopters -- to the mainstream way of developing software. All this time, the XP conference series has actively promoted agility and widely disseminated research results in this area. XP 2013 successfully continued this tradition. The 17 full papers accepted for XP 2013 were selected from 52 submissions and are organized in sections on: teaching and learning; development teams; agile practices; experiences and lessons learned; large-scale projects; and architecture and design.